At the intersection of language, gender, and religion: Self-reported linguistic ideologies and practices of Muslim women in Barcelona. (20th December 2021) - Ali, Farah
Abstract : Language use is notably connected to the construction and negotiation of gendered identity (Butler, 1993; Cameron, 1997; Norton, 2000; Menard-Warwick, 2009). However, the study of intersectional identities – such as gendered and religious identity – as it relates to linguistic behavior remains a relatively unexplored area of research. This study examines self-reported language use as a gendered practice among Muslim immigrant women in Barcelona (Catalonia, Spain). Using data collected from interviews with 34 Muslim women, this study looks at self-reported gendered roles, as well as the linguistic and gendered ideologies that are reflected in informants' beliefs about their own language use. Furthermore, this study provides evidence of informants expressing specific gender roles that stem from both the heritage and target language (Spanish/Catalan) communities, as reflected in informants' tendencies to interact primarily with other women and vary their speech depending on the gender and/or heritage identity of their interlocutors.